FINANCIAL TECHNOLOGY (FINTECH) PADA PERBANKAN SYARIAH: APLIKATIF DAN PERAN - Latifah, Eny; Abdullah, Rudi (JIAR : Journal Of International Accounting Research, 2022)
The research objective is to find out what applications are used by Bank in implementing Financial Technology and what is the role of Bank Muamalat Indonesia in implementing Fintech. The research method used is qualitative with a case study type. The results 1) The application applied by Bank in implementing Fintech is (a) Mobile banking called "Muamalat-DIN";(b)Muamalat Digital Integrated Access (MADINA); (c) Shar-e debit online; (d) Internet banking; (e) Phone banking; (f) Virtual accounts; (g) ATM (Automatic Teller Machine). 2) The role of Islamic Banking in FinTech is: (a) As a financial institution that implements Financial Technology; (b). Become a Financial Institution that always innovates to fulfill financial inclusion; (c). Islamic Financial Institutions that provide Excellent Service to the Community; (d). Financial Institutions presenting key features of regulatory initiatives set up to facilitate FinTech innovation (e). Encouraging Supervisory Potential Opportunities to Use Innovative Technologies; (f). Increasing cross-sectoral cooperation between bank supervisors and other relevant authorities: (g). Opening opportunities for international cooperation in the aspect of inter-bank supervision.